PENGARUH PENGGUNAAN SOFTWARE AKUNTANSI SYSTEM APPLICATION AND PRODUCT (SAP) DAN KUALITAS NILAI INFORMASI PELAPORAN KEUANGAN TERHADAP KEPUASAN PENGGUNA SOFTWARE AKUNTANSI (STUDI KASUS PADA PT. PLN (PERSERO) KANTOR WILAYAH ACEH-KOTA BANDA ACEH) - Wahyuddin Wahyuddin; Mira Afriani (Jurnal Akuntansi dan Keuangan, 2018)
This research aims to know influence of the use of System Application Product and ( SAP) accounting software and the quality of financial reporting information value to the satisfaction of the consumers of accounting software. This research use census method and the population is the employees at financial division, HRS&PUBLIC division, planning and technical field division. The respondents of  this research are the employees who apply the accounting software of System Application Product and ( SAP) at PT. PLN (PERSERO), Regional Office of Aceh-Banda Aceh city. The samples were taken using census sampling technique. The data were analysed using multiple linear regression analysis and hypothesis were tested using SPSS 17. The result are as follows: the usage of accounting software of System Application Product and ( SAP) has a signifcant effect on the satisfaction of consumer of accounting software, the quality of financial reporting information value has a significant effect on the satisfaction of consumer of accounting software, and the usage of accounting software of System Application Product and ( SAP) and quality of financial reporting information value has an significant effect on the satisfaction of consumer of accounting software. The further researcher should change the research variables, research object and use a better tool analysis in order to get more accurate data.